5y+6y-81=7y+102+66y

Simple and best practice solution for 5y+6y-81=7y+102+66y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y+6y-81=7y+102+66y equation:


Simplifying
5y + 6y + -81 = 7y + 102 + 66y

Reorder the terms:
-81 + 5y + 6y = 7y + 102 + 66y

Combine like terms: 5y + 6y = 11y
-81 + 11y = 7y + 102 + 66y

Reorder the terms:
-81 + 11y = 102 + 7y + 66y

Combine like terms: 7y + 66y = 73y
-81 + 11y = 102 + 73y

Solving
-81 + 11y = 102 + 73y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-73y' to each side of the equation.
-81 + 11y + -73y = 102 + 73y + -73y

Combine like terms: 11y + -73y = -62y
-81 + -62y = 102 + 73y + -73y

Combine like terms: 73y + -73y = 0
-81 + -62y = 102 + 0
-81 + -62y = 102

Add '81' to each side of the equation.
-81 + 81 + -62y = 102 + 81

Combine like terms: -81 + 81 = 0
0 + -62y = 102 + 81
-62y = 102 + 81

Combine like terms: 102 + 81 = 183
-62y = 183

Divide each side by '-62'.
y = -2.951612903

Simplifying
y = -2.951612903

See similar equations:

| 4a=3a+20 | | fx=(400+20x)(90-1x) | | (3q-8)(-9q+2)(q-2)=0 | | -2x^2=12x-14 | | 5+3*4-8+2*7= | | 2[9(6-5)]= | | (14x+5)(14x+5)=20 | | 2(x+4)+star=16 | | 5f=f+36 | | 5x+5(2x+10)=10x+12 | | 2(x+4)-5x=23 | | 3x+2star+x=x+6 | | 5x-2=-x+7+6 | | 5(y+5)-5y=31 | | -3+sy=17 | | 8x-1x=7x | | 32-(2c+4)=2(c+7)+c | | ax+by+c+2ax-3by+c+by-c= | | 5=(7-2)/3-x | | 2x^2-13=7x | | 5=7-2/3-x | | 3(2star)-3star+4=2star+5 | | 4a+2b+c=8 | | 12-4(6x-2)=8-(2x+5) | | 35=5u | | 2x+6=7-3x | | 97=215t+-16t^2 | | y=sin(5x+2) | | 7w-16w= | | 6c=4c+6 | | 5(k-3)-8=5k-(4k-3) | | 4x+3-5x= |

Equations solver categories